Peran Ulama dalam Pembaharuan Kurikulum Pendidikan di Aceh: Studi Pada Organisasi Persatuan Ulama Seluruh Aceh (PUSA) - A Amarullah; Khairul Fahmi (MAMBA'UL 'ULUM, 2026)
This article discusses the role of the Association of Ulama of All Aceh (PUSA), particularly in relation to the reform of the Islamic education curriculum in Aceh. Islamic education in this “Veranda of Mecca” has continued to undergo changes, both positive developments and setbacks, from the era of the sultanate to the period of revival following Indonesia’s independence. The author argues that the PUSA organization plays a crucial role in the reform of the Islamic education curriculum in Aceh. The author used the library research method to obtain data regarding the role of the PUSA organization. The results of the study indicate that the Aceh Ulama Association (PUSA) successfully integrated subjects, modernized the education system in Aceh, and established regulations for teachers, students, and prospective new students. This was done as a form of commitment to improve the quality of Islamic education in Aceh, while simultaneously enhancing the quality of learning, discipline, teaching effectiveness, and the development of human resources oriented toward societal progress.